Retrieving Information for Urgency Medical Services using Abundant Data Processing Method - Balaji, V; Dinagaran, D; Rajmohan, R (IJRDO -Journal of Computer Science Engineering, 2015)
The Internet of Things (IoT) is the interconnection of uniquely identifiable embeddedcomputing devices within the existing internet infrastructure. Delivering clinical information of patientat the point-of-care to physicians is critical to increase the quality of healthcare services, especially inemergency time. However, clinical data are distributed in different hospitals. It is sometimes difficultto collect clinical data of patient ubiquitously in case of urgency. In order to support the ubiquitouscontent accessing a resource model is first proposed to locate and get clinical data which are stored inheterogeneous hospital information systems using Hadoop Distributed File System. In the proposedmethod clinical data of patient is defined as resource with unique URL address. Related clinical data ofone patient is collected together to form a combinational resource, and could be accessed by physicianif authority is assigned to the physician, by using a mongo dB database technique efficiently in big dataapplications for better performance and scalability. This type of database support faster execution ofqueries compared to non-relational databases. By implementing the system that combines IoT with BigData is built to provide quick and effective for different patients.